Comparative study of bismuth composites obtained via pulsed laser ablation in a liquid and in air for photocatalytic application - Svetlichnyi, Valerii A.; Fakhrutdinova, Elena D.; Nazarova, Tatiana S.; Kulinich, Sergei A.; Vodyankina, Olga V. (Solid state phenomena)
In the present work, bismuth-based nanoparticles of various compositions were obtained by pulsed laser ablation of a metallic bismuth target in water and air using a Q-switch Nd:YAG laser (wavelength of 1064 nm, pulse duration of 7 ns, frequency of 20 Hz, and pulse energy of 160 mJ). Then the samples were annealed in air at temperatures up to 600°C. A comparative analysis of the obtained powders was carried out using methods of X-ray diffraction, transmission electron microscopy, specific surface area measurements, IR-Fourier and UV-Vis Spectroscopy. The photocatalytic activity of the synthesized materials in the process of Rhodamine B decomposition under irradiation of a LED source (375 nm) was also studied.